Customer Satisfaction in Relation to the Products and Services of Nagarjuna Herbal Concentrates Ltd (NHCL) - Mathew, Rincy V.; Sudha, G. (Indian Journal of Marketing, 2005)
For customer-centric companies, customer satisfaction is both a goal and marketing tool.Nagarjuna Herbal concentrates Ltd. (NHCL) is a leading ISO 9001: 2000 Ayurvedic company operating from Kerala. It is involved in the production and marketing of clinically proven, patented Ayurvedic products as well as Ayurvedic consumer products. The company is also having its own medical units with treatment and pharmaceutical services. The R&D facility of NHCL is approved by the drugs Controller, Kerala state. The company considers the customer as the "King" and customer satisfaction plays important roles in market growth, product diversification, market modification and above all retaining an intact customer base. The present paper is an effort to critically evaluate the feelings and responses of the customers of NHCL towards its product and services with a view to explore new avenues in marketing.